From Mathematics Learning to Character Building: A Pedagogical Study on the Internalization of Religious Moderation - Dona Dinda Pratiwi; Waluyo Erry Wahyudi; Cahniyo Wijaya Kuswanto (Jurnal Sipakatau: Inovasi Pengabdian Masyarakat, 2026)
Social dynamics in a multicultural society place education in a strategic position to foster moderate, inclusive, and sustainable religious attitudes from an early age. This study aims to analyze the process of internalizing religious moderation values in the Merdeka Curriculum and the Integrated Islamic School Network (JSIT) Curriculum, as well as its implications for character building among students at the kindergarten, elementary school, and junior high school levels. The research uses a descriptive analytical qualitative approach with a multi-site study design. Data were collected through observations of learning and school culture, semi-structured interviews with teachers and curriculum managers, and document analysis, then analyzed thematically using ATLAS.ti. The results of the study indicate that the internalization of religious moderation values is a pedagogical process that is gradual, contextual, and systemic. Although both curricula provide a relatively similar structural framework, the mechanisms of value internalization develop differently according to the developmental stages of students, ranging from concrete experiences and role models at the early stages to structured habits and value reflection at higher levels. Cross-level analysis confirms that learning, especially mathematics learning as a space for reasoning and social interaction, functions as the main medium for internalizing values through collaborative activities, problem solving, and class discussions that foster attitudes of fairness, tolerance for differences in thinking, and shared responsibility. Further analysis shows that continuous habituation acts as a connecting mechanism between learning and character building. This study concludes that the effectiveness of religious moderation education depends on the alignment of pedagogical strategies, the role of teachers as pedagogical agents, learning characteristics, and the developmental stages of students in the school learning ecosystem.